CASTLEMAN’S DISEASE IN THE LONG TERM FOLLOW-UP OF A PATIENT WITH NON HODGKIN’S LYMPHOMA: AN UNUSUAL PRESENTATION - Rajjyoti Das; Jagannath Dev Sharma; Manigreeva Krishnatreya; Amal Chandra Kataki (National Journal of Medical Research, 2014)
Castleman’s disease is a benign condition characterized by localized or generalized lymphadenopathy. It is an inherited disorder and usually seen concurrently with lymphomas. We present here a case of multi-centric hyaline vascular type of Castleman’s disease detected in the long term follow-up of a patient who was being previously treated for non Hodgkin’s lymphoma. In the long term follow-up of patient with lymphomas it can be a cause of lymph node enlargement bearing a clinical resemblance to recurrence of lymphoma. The diagnosis of should be made by a combination of clinical, radiological examination and histopathological examination with immunohistochemistry